Ethylene-dependent regulation of an α-l-arabinofuranosidase is associated to firmness loss in 'Gala' apples under long term cold storage. (1st September 2015) - Storch, Tatiane Timm; Finatto, Taciane; Pegoraro, Camila; Dal Cero, Joceani; Laurens, François; Rombaldi, Cesar Valmor; Quecini, Vera; Girardi, César Luís
Highlights: Arabinofuranosidase genes 1 and 3 transcription is not restricted to apple fruit. Arabinofuranosidase genes 1 and 3 are down regulated by 1-methylcyclopropene. Transcription levels of arabinofuranosidase gene 3 is higher than gene 1 in apples. ARABINOFURANOSIDASE3 contributes to enzyme activity in apples under cold storage. Arabinofuranosidase activity is associated to apple firmness loss in cold storage. Abstract: Fruit texture changes impair the quality of apples submitted to long term storage, especially under cold. The changes are due to cell wall modifications during ripening and senescence and are associated to ethylene. We have investigated the activity of α-l -arabinofuranosidase, a glycosyl hydrolase acting on the side chains of pectin in the cell wall and middle lamella. The transcription of arabinofuranosidase coding sequences 1 and 3 was investigated in plant organs and in response to ethylene, employing hormone application and 1-methylcyclopropene. The transcription of arabinofuranosidase genes is not restricted to fruits, although upregulated by ripening and ethylene. Transcripts of the genes were detected under cold storage up to 180 days. Similarly, arabinofuranosidase activity increased with rising levels of ethylene and under cold storage. Levels of ARABINOFURANOSIDASE3 transcripts were higher than those of ARABINOFURANOSIDASE1, suggesting that the first is an important contributor to enzyme activity and texture changes during cold storage.